Utilización de Residuos De Madera en Pequeños Talleres de Artesanía y Elaboración de Muebles en la Comunidad de Sarchí - Mata-Montero, Carlos; Medina-Escobar, María de Lourdes; Astorga, Eligio; Salas-Garita, Cynthia; Del Valle-Granados, Ignacio (Instituto Tecnológico de Costa Rica, 2010)
The transformation of wood for making furniture and crafts are an important source of income for the community; however, the waste generated from production processes represent an environmental, financial and space problem. The objective of this research was to contribute to the improvement of performance (financial, labor and environmental) of associated companies and COOPEARSA Muebleros and Artisans Association through the re-use of wood waste from the manufacturing process furniture and crafts. From the collection of information on the amount of waste and the review of the various alternatives available for the re-use of these, he raised the design and layout of a hybrid dryer developed with a gasification system incorporated with the which the community of artisans and furniture makers could get the benefit of drying wood already using both the waste disposal of the workshops. Market studies, technical and financial yield positive results achieved in implementing this technology.
Proyecto de Investigación. Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Seguridad Laboral e Higiene Ambiental; Escuela de Ingeniería Electromecánica; Escuela de Ingeniería Forestal, 2010
Keywords: Materia prima; Caracterización; Distribución; Desechos; Alternativas